PENGARUH BRAND AMBASSADOR DAN LABEL HALAL TERHADAP MINAT BELI PRODUK WARDAH DI DESA BAYAT ILIR KECAMATAN BAYUNG LENCIR - Ria Anggilia; Abd. Malik; Erwin Saputra Siregar (Jurnal Publikasi Ilmu Manajemen, 2023)
This research aims to determine the influence of brand ambassadors and halal labels on the interest in buying Wardah products in Bayung Lencir District, Bayat Ilir Village. This type of research uses quantitative research. The data used in this study is primary data obtained using data collection techniques from questionnaires. The sample obtained in this study was 102 respondents. The technique in sampling in this study used a non probability sampling method. Analyzed using multiple linear regression analysis. The results of the analysis of this study indicate that the brand ambassador variable has a partial influence on buying interest in Wardah products with a significant level of 0.010 where t count (2,611) > t tabele (1,660). The Halal Label variable does not have a partial effect on buying interest in Wardah products with a significant level of 0.253 where t count (1,149) > t tabele (1,660). Simultaneous test results, brand ambassador and halal label have an effect on Wardah product purchase interest with a significant level of 0.007.